Cloud microphysical relationships and their implication on entrainment and mixing mechanism for the stratocumulus clouds measured during the VOCALS project. Issue 10 (26th May 2015) - Yum, Seong Soo; Wang, Jian; Liu, Yangang; Senum, Gunnar; Springston, Stephen; McGraw, Robert; Yeom, Jae Min
Abstract Cloud microphysical data obtained from G‐1 aircraft flights over the southeastern Pacific during the Variability of the American Monsoon Systems Ocean‐Cloud‐Atmosphere‐Land Study Regional Experiment field campaign were analyzed for evidence of entrainment mixing of dry air from above cloud top. Mixing diagram analysis was made for the horizontal flight data recorded at 1 Hz and 40 Hz. The dominant observed feature, a positive relationship between cloud droplet mean volume (V) and liquid water content (L), suggested occurrence of homogeneous mixing. On the other hand, estimation of the relevant scale parameters (i.e., transition length scale and transition scale number) consistently indicated inhomogeneous mixing. Importantly, the flight altitudes of the measurements were significantly below cloud top. We speculate that mixing of the entrained air near the cloud top may have indeed been inhomogeneous; but due to vertical circulation mixing, the correlation between V and L became positive at the measurement altitudes in midlevel of clouds, because during their descent, cloud droplets evaporate, faster in more diluted cloud parcels, leading to a positive correlation between V and L regardless of the mixing mechanism near the cloud top.